Integrating the African Real Estate Market – An Agenda: The 18th AfRES Conference 2018
DOI: 10.15396/afres2018_145
|View full text |Cite
|
Sign up to set email alerts
|

Causal Relationship of N-REITs Dividend Yield and Money Market Indicators: A Case Study of Skye Shelter REIT

Abstract: This paper examines the relationship between Nigeria equity real estate investment trusts (REITs), with focus on Nigeria First REIT (Skye Shelter) and money market indicators (MMI), such as Treasury bill (TBR), Prime lending rate (PLR), Currency-in-Circulation (CIC), injection to corporate private sector (CPS) and Broad Money Supply to the economy (BMS) in the period 2008-2016 in an attempt to document the statistical significance of the indicators on N-REITs dividend returns. Design/Methodology/Approach-Quart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…For example, the 3 month's Treasury Bills provides a return of 8.5% and return on cash ranges between 4.5% and 10.5%. Olanrele et al (2018), in a study carried out to determine the causal relationship between N-REITs dividend yield and Money Market Indicators (MMI) such as T-Bills and Currency in Circulation (CIC) found a short-run causal relationship between N-REITs dividend yield and MMI. The computed KPSS and PP test-statistics as seen in Table 6 are integrated of order I(0).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the 3 month's Treasury Bills provides a return of 8.5% and return on cash ranges between 4.5% and 10.5%. Olanrele et al (2018), in a study carried out to determine the causal relationship between N-REITs dividend yield and Money Market Indicators (MMI) such as T-Bills and Currency in Circulation (CIC) found a short-run causal relationship between N-REITs dividend yield and MMI. The computed KPSS and PP test-statistics as seen in Table 6 are integrated of order I(0).…”
Section: Resultsmentioning
confidence: 99%
“…This is not in agreement with the findings of Niskanen (2012), which asserted that REITs provide good returns on investments. More recently, studies such as Olanrele, Adegunle and Fateye (2018), investigated the correlations between REITs and Money Market Indicators, such as Treasury Bills, among others. The Granger Causality tests conducted in the study revealed an insignificant long-run causal relationship, but a significant short-run causal relationship between N-REITs returns and Money Market Indicators.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A low supply of real estate units subsequently leads to higher demand which leads to increases in the value of the real estate through higher rents and leases. Similarly, Olanrele, Adegunle, & Fateye (2018) established that real estate investments in Nigeria were sensitive to interest rate changes but mostly dependent on the property life remaining.…”
Section: Relationship Between Real Estate Residential Property Prices...mentioning
confidence: 99%
“…Such studies include Niskanen (2012). More recently studies such as Olanrele, Adegunle and Fateye (2018) investigated the correlations between REITs and Money Market Indicators such as Treasury Bills among others. A group of studies conducted in South Africa by Akinsomi, Kola, Ndlovu and Motloung (2016) investigated the performance of the broad based black economic empowerment (BBBEE) of both listed and delisted property firms in South Africa.…”
Section: Literature Reviewmentioning
confidence: 99%